Monitoring and Risk Assessment of Eight Polycyclic Aromatic Hydrocarbons (PAH8) in Daily Consumed Agricultural Products in South Korea. (21st April 2022) - Kim, Wonjun; Choi, Jisu; Kang, Hwa Jeong; Lee, Jo-Won; Moon, Bokyung; Joo, Yong-Sung; Lee, Kwang-Won
Abstract: Agricultural products are consumed as major staple foods; these are the main factors responsible for polycyclic aromatic hydrocarbon (PAH) exposure to humans. We analyzed the concentrations of eight PAHs (PAH8) in commonly consumed 359 agricultural samples that are commonly consumed in Republic of Korea. These food samples were divided into four groups (fatty-solid, fatty-liquid, nonfatty-solid, and nonfatty-liquid) and eight different food categories (cereals, potatoes, pulse crops, seeds and nuts, vegetables, mushrooms, fruits, and regional tap water). The chronic daily intake and margin of exposure (MOE) were estimated based on daily consumption data and benzo[a]pyrene equivalents. In our total diet studies, the major contributor to the total PAH8 concentration (ΣPAH8) in agricultural samples was dried jujube (2.32 μg/kg), followed by griddled milk bread (1.25 μg/kg) and stir-fried black sesame (1.17 μg/kg). The integrated toxic equivalent concentrations based on BaP (ΣTEQ bap ; integrated toxic benzo[a]pyrene equivalent quantity) considering the relative toxicity, ranged from 0.12 and 1.6 μg/kg. The PAH8 risk assessment in agricultural products was expressed as the MOE value. The worst scenario (when Not Detected = Limit of Detection) showed the interpretation of the MOE result as a 'possible concern' to consume bread products (bread, rye bread, milk bread, and cornbread). The preceding experiments were carried out mainly on commercially processed foods and their raw foods. Unlike such routine testing, our total diet study-based monitoring is designed to monitor PAH8 levels in which agricultural products are analyzed after being processed as usual consumption.